High wet-bulb temperatures, time allocation, and diurnal patterns of breastfeeding in Bangladeshi fisher-traders - Kathrine Starkweather; Haley Ragsdale; Margaret Butler; Fatema T. Zohora; Nurul Alam (Annals of Human Biology)
Background Climate change is a growing threat to population health, with dangerous combinations of heat and humidity increasing in frequency, particularly in South Asia. Evidence suggests that high temperatures and heat stress influence breastfeeding behaviour and may lead to suboptimal infant and young child nutrition.Aim Few studies have quantified the relationship between ambient heat and breastfeeding. Here we evaluate associations between wet-bulb temperature and daily breastfeeding patterns in a rural community in Bangladesh.Subjects and methods We used 23 months of daily time-diary data from 68 maternal-child dyads and regional wet-bulb temperatures to test the hypothesis that increased heat and humidity negatively influence breastfeeding outcomes among Shodagor fisher-traders.Results We found that higher wet-bulb temperatures predicted reduced daily breastfeeding time allocation, particularly among fishers, and drove shifts towards increased night-time and decreased mid/late morning feeding. Maternal occupation and the interaction of child age with heat strongly influenced diurnal breastfeeding patterns.Conclusion These results highlight an important role of maternal work on infants’ vulnerability to environmental stress. Dyads’ ability to behaviourally compensate for extreme heat may be constrained by extended heatwaves, humidity, and economic circumstances, suggesting that climate change will likely exacerbate heat-related risks to global child health going forward.